Effects of microgravity exposure and fructo-oligosaccharide ingestion on the proteome of soleus and extensor digitorum longus muscles in developing mice - Takashi Ohira (Nature Portfolio, 2021)
Abstract Short-chain fatty acids produced by the gut bacterial fermentation of non-digestible carbohydrates, e.g., fructo-oligosaccharide (FOS), contribute to the maintenance of skeletal muscle mass and oxidative metabolic capacity. We evaluated the effect of FOS ingestion on protein expression of soleus (Sol) and extensor digitorum longus muscles in mice exposed to microgravity (μ-g). Twelve 9-week-old male C57BL/6J mice were raised individually on the International Space Station under μ-g or artificial 1-g and fed a diet with or without FOS (n = 3/group). Regardless of FOS ingestion, the absolute wet weights of both muscles tended to decrease, and the fiber phenotype in Sol muscles shifted toward fast-twitch type following μ-g exposure. However, FOS ingestion tended to mitigate the μ-g-exposure-related decrease in oxidative metabolism and enhance glutathione redox detoxification in Sol muscles. These results indicate that FOS ingestion mildly suppresses metabolic changes and oxidative stress in antigravity Sol muscles during spaceflight.